2021
DOI: 10.3390/ijerph18189933
|View full text |Cite
|
Sign up to set email alerts
|

Robots in Healthcare? What Patients Say

Abstract: In this paper, we analyse patients’ perspectives on the introduction of artificial intelligence (AI) and robotic systems in healthcare. Based on citizens’ experiences when hospitalised for COVID-19, we explore how the opinions and concerns regarding healthcare automation could not be disassociated from a context of high pressure on the health system and lack of resources, and a political discourse on AI and robotics; a situation intensified by the pandemic. Thus, through the analysis of a set of interviews, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The authors of one review found that older people had more positive than negative attitudes towards robots in health care [22]. However, an interview study revealed that patients prefer human interaction in care on the one hand, but also advocate the use of robots for some caregiving tasks [23]. Quantitative surveys in Germany showed that 40% of people over the age of 70 years fundamentally rejected assistance by robots, whereas 82% of older people could imagine the use of robots as long as this allows them to live at home longer [24].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of one review found that older people had more positive than negative attitudes towards robots in health care [22]. However, an interview study revealed that patients prefer human interaction in care on the one hand, but also advocate the use of robots for some caregiving tasks [23]. Quantitative surveys in Germany showed that 40% of people over the age of 70 years fundamentally rejected assistance by robots, whereas 82% of older people could imagine the use of robots as long as this allows them to live at home longer [24].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have concentrated the objective of their analysis on the perception of technologies or robots in samples of health professionals and patients, both potential end users of these devices [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, some research has delved into the perspective of professionals and patients in relation to the use of robotics in healthcare and, more specifically, in relation to COVID-19. [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The danger of over-reliance and excessive dependence on such systems should also be highlighted and investigated, for this could lead to serious effects such as the deskilling and desensitization of healthcare personnel. In other words, some decision-making processes could be influenced by new technologies, undermining the essential doctor-patient relationship ( 39 ).…”
Section: Limits and Criticalitiesmentioning
confidence: 99%